Fase-Fase Bulan (Kajian Akurasi Perhitungan Data New Moon dan Full Moon dengan Algoritma Jean Meeus untuk Bulan Kamariah) - li'izza diana manzil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Generally, the Moon has four distinct phases, namely: New Moon, First Quarter, Full Moon, and Last Quarter. In contrast to the other two phases, the New Moon and Full Moon phases are frequently used in the studies discussing Qamariah months since they cope with Muslim worship such as salat (prayers), fasting, hajj, and so on. Various methods have been employed for the calculation of the New Moon and Full Moon, ranging from ‘taqribi’, ‘haqiqi’, and contemporary methods. The calculation of Jean Meeus’ algorithm is often presented in those studies. This kind of calculation is carried out to explore the Julian Day (JD) investigating when New Moon and Full Moon occur in the Qamariah months. The Jean Meeus’ algorithm data were taken into account of Ramadhan 1430 H. The calculation result was compared to the ephemeris method and ‘mawaqit’ application to examine the level of accuracy. This study promotes that the difference is not too significant so that the calculation result is able to be used as the ‘hisab’ (calculation) of the first day of Qamariah months.